If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -23 = -3x Combine like terms: 20 + -23 = -3 -3 = -3x Solving -3 = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -3 + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 -3 + 3x = 0 Add '3' to each side of the equation. -3 + 3 + 3x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 0 + 3 3x = 0 + 3 Combine like terms: 0 + 3 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 6x-8=3.5 | | 17x-23=12 | | (x-7)(x-5)(x+4)(x+6)=608 | | 17x-32=34 | | b_4+8=-40 | | x^2=2x^2-8x+8 | | ln(y)=ln(x)+ln(x+1)+ln(C) | | -7+x=5 | | 24x-32=14 | | -.4x+6.4=8 | | 13-4f=18 | | 4x+-20=-40 | | x_8-4=7 | | 37=4w+5 | | 4(x-1)-x=11 | | 2x+y=1.10 | | 121=34+yx+y+34+180 | | 0=4x^3+3x^2-6x | | (3*-2)4=x | | 3x+24=7x+3 | | 2x+2=3x-15+9 | | 50x+20=8(40) | | 2x-11=7x | | 2x-11=7c | | 6st*2st*t*t*t= | | 0.7z-11.9=-0.3z+0.15 | | 3a-4=2 | | 36-3(4r-8)=0 | | 247*.50= | | 14-2n= | | 1x+4y=-4 | | 0.5x+10=2.4x+3.4 |